(3EjVGM GdOQI GdeVjI aj bQGAGJ GdKdGKI GdUMjMI GdeQVjIs - (3YKeGf Hf YeQ Hf CHj HcQ GdfGTQj, Yaja GdOjf , J (B848 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi Jhdi MaX cJGHg Gdecfhf , abGd (B: (3EfGfMf fRdfG GdPcQ hEfG dg dMGaXhf (B" (3hbGd JYGdi ai GdbQBf GdeLjO (B: (3dGjCJjg GdHGWd s
(3BNQgG (B:s
(3hQGbHJ faSi cd Mjf hdMXI hdGbjJ QHi dG Ydi hdG djG Je EjVGM GdOQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdfSNI HgG MhGTs
(3HChdgG HebOGQ hQbJjf HYV GdJQGLes
(3cJHJ GdYfGhjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs